Controversy over the Customary Land Ownership: A Political Analysis - Khandakar Q. Elahi (Jurnal Mengkaji Indonesia, 2026)
Abstract: This article examines the persistent controversy surrounding customary land ownership through a political and philosophical lens. While existing scholarship has predominantly approached customary land tenure from economic and administrative perspectives, this study argues that the core issue is fundamentally political because property rights derive from state authority and legal recognition. By tracing the historical evolution of customary land tenure and analyzing the concepts of property and sovereignty through John Locke’s theory of property and the Locke–Rousseau conception of the nation-state, the article investigates the implications of decolonization and state formation for customary land governance. The findings suggest that the transition from clan-based political organizations to modern nation-states fundamentally transformed the basis of land ownership. Consequently, claims of communal ownership by clans over extensive customary territories are conceptually inconsistent with the principles of the nation-state. The study proposes a twofold reform framework: first, a constitutional recognition of the state as the ultimate owner of national land resources; and second, a cadastral and landform-based approach to classify land into public and private ownership categories. This political reinterpretation provides a coherent framework for resolving customary land disputes, improving land governance, strengthening tenure security, and promoting socioeconomic development in countries where customary land tenure remains dominant. Purpose: To analyze the controversy over customary land ownership from a political-philosophical perspective and develop a coherent framework for land tenure reform based on property rights theory and nation-state principles. Design/Methodology/Approach: This study employs qualitative political analysis grounded in historical institutionalism and political philosophy. It utilizes an extensive literature review, historical records, policy documents, and theoretical analysis based on Locke’s property theory and the Locke–Rousseau conception of the nation-state. Findings: The study finds that customary land ownership conflicts stem from an inconsistency between traditional clan-based governance structures and modern nation-state institutions. The formation of nation-states transferred territorial sovereignty to national governments, rendering communal clan ownership claims over extensive customary lands conceptually incompatible with contemporary statehood. A constitutional and cadastral reform framework is therefore necessary. Originality/value: This article offers a novel political-philosophical interpretation of customary land tenure by linking property rights, sovereignty, and nation-state formation. It moves beyond conventional economic analyses and provides an original framework for resolving customary land ownership disputes in postcolonial societies.